2021
DOI: 10.1038/s41419-021-03722-8
|View full text |Cite
|
Sign up to set email alerts
|

YAP inhibits autophagy and promotes progression of colorectal cancer via upregulating Bcl-2 expression

Abstract: Colorectal cancer (CRC) is one of the most aggressive and lethal cancers. The role of autophagy in the pathobiology of CRC is intricate, with opposing functions manifested in different cellular contexts. The Yes-associated protein (YAP), a transcriptional coactivator inactivated by the Hippo tumor-suppressor pathway, functions as an oncoprotein in a variety of cancers. In this study, we found that YAP could negatively regulate autophagy in CRC cells, and consequently, promote tumor progression of CRC in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…The depletion of CRB3 can inhibit the Hippo pathway and lead to increased nuclear localization of YAP [ 30 , 31 , 43 ]. The Hippo pathway plays a crucial role in regulating CRC progression [ 44 47 ]. In the present study, we also observed that CRB3 knockdown inhibited the Hippo pathway and increased the nuclear localization of YAP, suggesting that CRB3 regulates CRC progression through the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of CRB3 can inhibit the Hippo pathway and lead to increased nuclear localization of YAP [ 30 , 31 , 43 ]. The Hippo pathway plays a crucial role in regulating CRC progression [ 44 47 ]. In the present study, we also observed that CRB3 knockdown inhibited the Hippo pathway and increased the nuclear localization of YAP, suggesting that CRB3 regulates CRC progression through the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer, aberrant signals from cancer-associated pathways, such as WNT and activated KRAS, activate Hippo to promote tumor growth and metastasis [ 28 ]. It is intriguing that the apoptosis inhibitor BCL2 is among the target genes of YAP1, a fact that could contribute to YAP1 dependency in 20q11.21 amplified cancers, given that the related BCL2L1 protein is dysregulated in these cancers [ 29 ]. Thus, interruption of Hippo signaling could impede, at least partially, aberrant cancer cell signals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Bcl-2 family proteins inhibit VSP34-BECN1 complex activation [ 56 ]. A recent paper demonstrated in a colorectal carcinoma (CRC) model that the YAP/TEAD complex binds to upregulate Bcl-2 expression, which leads to autophagy inhibition [ 57 ]. This suggests that additional pathways may play a role in autophagy regulation.…”
Section: Autophagymentioning
confidence: 99%